A most wanted man [compact disc, unabridged] - Le Carré, John, 1931-2020- (Simon & Schuster Audio, 2008)
A half-starved young Russian man in a long black overcoat is smuggled into Hamburg in the dead of night. He has an improbable amount of cash hidden in a purse around his neck and he says his name is Issa. Annabel, an idealistic young German civil rights lawyer, is determined to save Issa from deportation. Soon her client's survival becomes more important to her than her own career--or safety.